PENGARUH MODEL PEMBELAJARAN DAN MINAT BELAJAR TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA: DOI: https://doi.org/10.37850/cendekia.v12i1.114. - Yusri Firdaus (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
The purpose of this study was to determine the effect of learning models on students' creative thinking abilities in mathematics, the influence of learning interest on students' creative thinking abilities and the interaction of learning models and learning interests on students' creative thinking abilities. The research method used was an experiment conducted at schools in Serang District, namely at SMAN 1 Pontang and SMAN 1 Tirtayasa class XI IPA even semester by taking a sample of one school as an experimental class and one other school as a control class with the population being all students of class XI IPA and the samples are students of class XI IPA 4 of SMAN 1 Pontang and class XI IPA 1 of SMAN 1 Tirtayasa with a random sampling technique that is a random sampling strategy based on the assumption that members of the population are homogeneous. Data is collected by testing the ability to think creatively and through interest in learning mathematics. Analysis of data with descriptive statistical methods, with two-way ANAVA test. This research was conducted in March to June 2014. The results of the study with the two-way ANAVA test showed: (1). There is an influence of learning models on students' creative mathematical thinking abilities, this can be proven by the value of F = 37,202 and sig.0,000 <0.05 (2). There is an influence of interest in learning on students' mathematical creative thinking abilities. This can be proven by the value of F = 136,463 sig. = 0.00 <0.05 (3). There is no effect of interaction between learning models and learning interest on students' creative mathematical thinking abilities. This can be proven by the value of F = 1,293 sig. 0.260> 0.05. The implication of this is that an educator must be able to design or design learning activities effectively, attractively and fun with a variety of learning methods in accordance with the learning material and students 'abilities in an effort to improve students' mathematical creative thinking abilities. Jigsaw model can be a reference in learning activities.The purpose of this study was to determine the effect of learning models on students' creative thinking abilities in mathematics, the influence of learning interest on students' creative thinking abilities and the interaction of learning models and learning interests on students' creative thinking abilities. The research method used was an experiment conducted at schools in Serang District, namely at SMAN 1 Pontang and SMAN 1 Tirtayasa class XI IPA even semester by taking a sample of one school as an experimental class and one other school as a control class with the population being all students of class XI IPA and the samples are students of class XI IPA 4 of SMAN 1 Pontang and class XI IPA 1 of SMAN 1 Tirtayasa with a random sampling technique that is a random sampling strategy based on the assumption that members of the population are homogeneous. Data is collected by testing the ability to think creatively and through interest in learning mathematics. Analysis of data with descriptive statistical methods, with two-way ANAVA test. This research was conducted in March to June 2014. The results of the study with the two-way ANAVA test showed: (1). There is an influence of learning models on students' creative mathematical thinking abilities, this can be proven by the value of F = 37,202 and sig.0,000 <0.05 (2). There is an influence of interest in learning on students' mathematical creative thinking abilities. This can be proven by the value of F = 136,463 sig. = 0.00 <0.05 (3). There is no effect of interaction between learning models and learning interest on students' creative mathematical thinking abilities. This can be proven by the value of F = 1,293 sig. 0.260> 0.05. The implication of this is that an educator must be able to design or design learning activities effectively, attractively and fun with a variety of learning methods in accordance with the learning material and students 'abilities in an effort to improve students' mathematical creative thinking abilities. Jigsaw model can be a reference in learning activities.